TRENDS IN OFFICE AND AMBULATORY BP ACROSS PEDIATRIC AGE. (April 2021) - Lurbe, Empar; Alvarez, Julio; Torro, Maria Isabel; Redon, Josep; Aguilar, Francisco; Redon, Pau
Abstract : Objective: ABPM is gaining ground in the assessment of BP in children and adolescents, becoming an aid for diagnosis and management of HTN. The 24-hours ABPM values obtained have generally been higher than those of their office BP counterparts, however the differences across the pediatric age have not been analyzed. The objective of the present study was to assess trends in office and 24-hours in children and adolescents. Design and method: Two thousand two hundred and sixty-four BP assessments (office and 24h-ABPM) were performed in 778 Caucasians youth of both sexes (387 females), of European origin, from 5 to 18 years of age (mean age 10.9 3.3 years) in the absence of antihypertensive treatment. Office BP was measured in the non-dominant arm and the three measurements were averaged for analysis. The same day, 24h-ABPM was performed and the averages of the valid readings for 24 h, daytime and nighttime, respectively, were calculated. Differences in trends of office and 24-hours ABPM, according to age and sex were analyzed using the slope of the regression lines. Results: Total ABPM measurements were 72+/- 14. Overall 24-hour SBP was higher than the office counterparts, however the magnitude of the differences changes according to age and sex (figure). In girls, the gap between office SBP and 24-hour SBP slightly reduces over the years, in contrast in boys the gap disappears at 15 years and thereafter. The slope of the regression lines was not significant in girls (ß 0.736 0.078 vs 1.199 0.284) while achieving statistically significance in boys (ß 0.395 0.0022 vs 0.759 0.062). Figure. No caption available. Conclusions: Differences in trends between office and ABPM are observed across age in both sexes. The reasons that fully explain this, need to be clarified. Disparities in trends may impact on the diagnosis of white-coat and masked HTN.